(untitled) (Journal of Management and Social Sciences, 2019)
This paper appraises Sulh (Reconciliation) as an alternative mechanism for resolving marital dispute in Ilorin, Kwara state of Nigeria. Cases of marital conflict among Muslim couples are very rampant in the city, leading to a significant rise in the spate of divorce, separation, single parenthood and domestic violence. This paper identifies the sources and effects of marital dispute on the family in Ilorin and discusses the simulative methods of using Sulh for resolving such dispute. The study relies on secondary data by analyzing existing works on the subject matter. The paper finds that the primary sources of conflict among Muslim couples in Ilorin include incompatible marital vision, unmet expectations, financial difficulty, job loss and bareness. The use of Sulh by Muslim mediators in Ilorin follows the Shari’ah (Islamic law) method of mediation that includes solicited or unsolicited intervention of external mediator, identification of conflict issues and resolution of conflict through pleas and soft bargaining. It is concluded that the application of Sulh in Ilorin, though with its limitations, is a credible alternative dispute resolution mechanism with promising outcomes. The Kwara state government should introduce Sulh to decongest the conventional courts and improve the alternative justice system in Ilorin.